Onobrychis garinensis (Hedysareae, Fabaceae), a new species from Iran - Dehshiri, Mohammad Mehdi (Phytotaxa, 2019)
Onobrychis garinensis sp. nov. is described from Garin Mountain near the Nurabad city (Lorestan Province) in the western part of Iran. The new species differs from O. alamutensis in its longer stipules and pod crest, and shorter corolla parts. The IUCN threat category of O. garinensis is determined as “CR (Critically Endangered)”.